2013
DOI: 10.1098/rsbl.2013.0839
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the protection of host immune systems by a polyembryonic parasitoid

Abstract: Endoparasitoids have the ability to evade the cellular immune responses of a host and to create an environment suitable for survival of their progeny within a host. Generally, the host immune system is suppressed by endoparasitoids. However, polyembryonic endoparasitoids appear to invade their hosts using molecular mimicry rather than immune system suppression. It is not known how the host immune system is modified by polyembryonic endoparasitoids. Using haemocyte counts and measurement of cellular immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The differential induction in this case was attributed to increased feeding in the parasitized caterpillars ( 13 ). In contrast to parasitoids that carry polydnavirus symbionts, this particular parasitic wasp maintains and even enhances the host immune system ( 14 ). This wasp species is in the Encyrtidae family, members of which do not possess polydnavirus symbionts.…”
mentioning
confidence: 99%
“…The differential induction in this case was attributed to increased feeding in the parasitized caterpillars ( 13 ). In contrast to parasitoids that carry polydnavirus symbionts, this particular parasitic wasp maintains and even enhances the host immune system ( 14 ). This wasp species is in the Encyrtidae family, members of which do not possess polydnavirus symbionts.…”
mentioning
confidence: 99%
“…Our recent study showed that male C. floridanum cancels the host-immune suppression of G. pallipes , whereas their female counterparts do not 26 . The humoral factor produced by the male C. floridanum –parasitized hosts might be multifunctional or multicomponent and related to host immune enhancements.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, total hemocyte counts of Chilo suppressalis larvae in the late stages increased after parasitism by Cotesia chilonis , but venom alone did not cause alteration in the hemocyte counts (Teng et al., ). In contrast, a reduction or no change in hemocyte population by parasitizaiton or venom of parasitoids regardless of PDV association was documented (Nishikawa, Yoshimura, & Iwabuchi, ; Rivers, Ruggiero, & Hayes, ; Teramoto & Tanaka, ; Yu et al., ). These indicate that there is diverse way of hosts hemocyte population change induced by parasitism and venom of parasitoids from different evolutionary classes, which depends on the specific evolutionary relationship between host and parasitoid.…”
Section: Discussionmentioning
confidence: 99%